(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The objective of this study was to develop solid dispersions of Nifedipine which has low aqueous solubility and bioavailability. Preliminary solubility studies were carried out using various hydrophilic polymers. The formulations were then optimized and evaluated by in-vitro dissolution studies, X-ray diffraction, FTIR and SEM. Formulation with 1:4:2 ratios of Nifedipine, Labrosol and SLS was found to be the best as it possessed better drug release properties compared to pure drug and other physical mixtures. The optimized formulation SD12 was found to have better drug release of 98.74 ± 5.19% in 90 minutes. From FTIR studies no interaction was takes place between drug and polymers. XRD peaks indicate the successful transformation of drug from crystalline to amorphous form. The final results indicate that the solid dispersion of Nifedipine remained stable over 90 days.